2016
DOI: 10.1016/j.urolonc.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Patients with ClearCode34-identified molecular subtypes of clear cell renal cell carcinoma represent unique populations with distinct comorbidities

Abstract: Purpose The 34-gene classifier, ClearCode34, identifies prognostically distinct molecular subtypes of clear cell renal cell carcinoma (ccRCC) termed ccA and ccB. The primary objective of this study was to describe clinical characteristics and comorbidities of relevance in patients stratified by ClearCode34. Patients and Methods In this retrospective analysis, 282 patients from Moffitt Cancer Center with ccRCC with gene expression analyses of the primary tumor were identified and ClearCode34 was applied to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…34-gene classifier (ClearCode34), which was a authoritatively subtyped predictor for classifying clear cell RCC according to good risk (ccA) and poor risk (ccB) subtype for assigning clear cell RCC patient and built a subtype-inclusive model to analyze patient survival outcomes according to risk stratification [9, 32]. The ClearCode34 classifier was applied for RNA-sequencing of data from 380 nonmetastatic clear cell RCC samples from TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…34-gene classifier (ClearCode34), which was a authoritatively subtyped predictor for classifying clear cell RCC according to good risk (ccA) and poor risk (ccB) subtype for assigning clear cell RCC patient and built a subtype-inclusive model to analyze patient survival outcomes according to risk stratification [9, 32]. The ClearCode34 classifier was applied for RNA-sequencing of data from 380 nonmetastatic clear cell RCC samples from TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular subtyping of primary ccRCC tumors based on gene expression profiles has shown that ccRCC tumors can be classified into molecular subtypes that are significantly associated with outcome [6,7,11,12]. While this work was revolutionary and helps to understand the molecular underpinnings of ccRCC, there are important practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most important, this classification represents clinically distinct subtypes, with ccB tumors demonstrating increased tumor size, grade, and rate of metastasis as well as decreased recurrence‐free and overall survival in multiple data sets . In addition, these molecular subtypes feature distinct metabolic patterns, with the aggressive ccB tumors demonstrating increased glucose uptake on imaging . However, the other clear finding from that study was that individual tumors can harbor both ccA and ccB components, making this classification strategy difficult for informing therapeutic selection, although it has emerged as a strong prognostic indicator in numerous studies .…”
Section: The Evolution Of Rcc Subclassification: a Path Of “Splitting”mentioning
confidence: 99%
“…41 However, the other clear finding from that study was that individual tumors can harbor both ccA and ccB components, making this classification strategy difficult for informing therapeutic selec-tion, although it has emerged as a strong prognostic indicator in numerous studies. 40,42 Other investigators have successfully merged gene expression data with metabolomics profiling to parse clear cell RCC into multiple molecular subtypes, including an aggressive cohort with increased glutathione metabolism. 43 Finally, building off the results from large-scale genome sequencing projects, another schema has emerged that focuses on 2 of the more commonly mutated genes in clear cell RCC: protein polybromo-1 (PBRM1 [also called BAP180]) and BRCA1-associated protein 1 (BAP1).…”
Section: Molecular Subtypes Of Rccmentioning
confidence: 99%